Patina of Sound: Valuing Vinyl Records as Relics of Aged Interaction - Brandon Polite; Elizabeth Scarbrough (ESPES, 2025)
In Things: In Touch with the Past (2019), Carolyn Korsmeyer builds on her earlier work in which she argues that our tactile interactions with objects connect us to the past, enriching our aesthetic experiences and imbuing artifacts with deeper meaning. Building on these insights, our paper addresses the puzzle of why some individuals prefer vinyl records despite the availability of music in sonically superior and cheaper digital formats. We argue that the physical act of handling records with care, being in touch with objects with unique histories, the traces of use and age that manifest in how they sound, and the extra effort involved in playing them contribute aesthetic dimensions to the experience of listening to music on vinyl that digital formats lack, which accounts for vinyl’s unique appeal.